القيم البلاغية في ثلاثيات البردة وانتشارها في اندونيسيا ومصر: دراسة موازنة - Wardani, Yaniah (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2023)
The rise of poets from every generation wrote poems in praise of the Prophet Muhammad SAW called Kasidah Burdah. However, due to limited information, not all literary works of the Kasidah Burdah are known. Literary scholars and researchers conclude into three great Burdah or known as